CityMii - An integration and interoperable middleware to manage a Smart City - Cecílio, José (2018)
Modern cities are supported by multiple heterogeneous IT systems deployed and managed by distinct agents. In general, those systems use old, dependent and non-standardized technologies, which make them legacy and incompatible systems. As smart cities are moving toward a fully centralized management approach, the lack of integration among systems raises several problems. Since they are independent, it is not easy to correlate information from different systems and put it together to work in order to achieve application goals. The collaboration among different systems enables an agent to offer new functionalities (services or just information about the city) that cannot be provided by any of these systems working as individual entities. The goal of this paper is to propose an integration middleware to support the management of Smart Cities in a dynamic, transparent and scalable way. The proposed middleware intends to support interoperability among different systems operating in a city.